Similarities between Muslims and Infils in punishment comparative analysis study - Husni, Ahmad Muhammad; Muhammad Husni, Amin (Zes Rokman Resources (2131022-P), 2025)
Islam emphasizes justice in implementing and carrying out a punishment. Every criminal who commits a crime should be given a punishment that is appropriate according to the rules and guidelines set by the shara'. Punishment in Islam is not intended to take revenge and oppress the offender, but punishment is for the good of the criminal himself and at the same time to protect the interests of society. In the implementation of punishment, the principle of equality is the main basis without distinguishing between every individual Muslim and non-Muslim. However, the principle of equality in punishment must be appropriate and not oppress the criminal. Therefore, the researcher wants to study whether there are similarities and differences of opinion among scholars regarding punishment between Muslims and infidels in the punishment of hudud, qisas and takzir. This study is a qualitative study, namely by studying books that discuss the punishment imposed on Muslims and infidels. As a result of this study, the researcher found that not all punishments imposed on infidels are similar to Muslims. However, there is also an opinion that says that infidels receive the same punishment as Muslims. In addition, there are also punishments that are only specific to Muslims such as hudud punishment, while infidels are exempt from hudud punishment and judges can choose to reject the case to the civil court or implement hudud punishment also to infidels who commit offenses under hudud punishment. Takzir punishment also has many similarities because this punishment is based on judges and the federal constitution. People who believe in Allah swt must accept the orders set by Allah which are written in the Quran and hadith. A constitution that does not threaten and challenge the integrity of the Islamic religion and the sanctity of Allah's law and does not deviate from the Islamic faith and is also considered good by Muslims should be accepted and lived as a valid constitution in terms of shara' law. Muslims and non-Muslims living in Islamic countries must comply with what Islam has outlined so that society can live in peace and tranquility. In addition, society can also live their lives without fear and phobia if society can follow and respect everything that Islam has taught.